2010
DOI: 10.1007/s11934-010-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Residency Training Program Paradigms for Teaching Robotic Surgical Skills to Urology Residents

Abstract: The advent of laparoscopic and robotic techniques for management of urologic malignancies marked the beginning of an ever-expanding array of minimally invasive options available to cancer patients. With the popularity of these treatment modalities, there is a growing need for trained surgical oncologists who not only have a deep understanding of the disease process and adept surgical skills, but also show technical mastery in operating the equipment used to perform these techniques. Establishing a robotic pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…The complication rate according to Clavien classification of our study is comparable with that of a previous study of 200 initial cases reported by Jeong et al; however, the rate of severe complications other than Clavien I was much less in our study when compared with that report [17]. The structured program for the certification of console surgeons in the MISC and our original step-by-step training program referenced by a previous study [18] has been suggested to minimize the severe complications and the requirement of open conversion operations. 2) BCR and PSM rate: Because the follow-up duration is relatively short in our patient cohort, oncological control was only been evaluated by PSM rate to date.…”
Section: Discussionsupporting
confidence: 87%
“…The complication rate according to Clavien classification of our study is comparable with that of a previous study of 200 initial cases reported by Jeong et al; however, the rate of severe complications other than Clavien I was much less in our study when compared with that report [17]. The structured program for the certification of console surgeons in the MISC and our original step-by-step training program referenced by a previous study [18] has been suggested to minimize the severe complications and the requirement of open conversion operations. 2) BCR and PSM rate: Because the follow-up duration is relatively short in our patient cohort, oncological control was only been evaluated by PSM rate to date.…”
Section: Discussionsupporting
confidence: 87%
“…As theoretical and technological advances continue to push the boundaries of what constitutes general urology training, residency programmes must continue to adapt both their curriculum content and delivery of content to address potential shortfalls [6]. One response to this challenge could be the introduction of subspecialist training early into the residency programme, such that more nuanced proficiency in open, robotic/laparoscopic or endoscopic urology can be developed by the completion of mandated training.…”
Section: Discussionmentioning
confidence: 99%
“…12 Heightened expectations from patients and medico-legal implications, as well as demands from hospital administrators to maximize results, mean that there is a limited opportunity for residents to train with the system. 13 Even more significant is the lack of any standardized competence-based training curriculum, which has been consistently underlined in successive literature. 14,15 the new training curriculum Guzzo et al and Shah et al proposed three essential phases in a structured robotics training program: preclinical phase, bedside assistant phase and operative console phase.…”
Section: Feature Article Challengesmentioning
confidence: 99%